A Novel Fucose-binding Lectin from Photorhabdus luminescens (PLL) with an Unusual Heptabladed β-Propeller Tetrameric Structure - Kumar, Atul; Sýkorová, Petra; Demo, Gabriel; Dobeš, Pavel; Hyršl, Pavel; Wimmerová, Michaela (The Journal of biological chemistry, 2016)
Photorhabdus luminescens is known for its symbiosis with the entomopathogenic nematode Heterorhabditis bacteriophora and its pathogenicity toward insect larvae. A hypothetical protein from P. luminescens was identified, purified from the native source, and characterized as an l-fucose-binding lectin, named P. luminescens lectin (PLL). Glycan array and biochemical characterization data revealed PLL to be specific toward l-fucose and the disaccharide glycan 3,6-O-Me2-Glcβ1-4(2,3-O-Me2)Rhaα-O-(p-C6H4)-OCH2CH2NH2 PLL was discovered to be a homotetramer with an intersubunit disulfide bridge. The crystal structures of native and recombinant PLL revealed a seven-bladed β-propeller fold creating seven putative fucose-binding sites per monomer. The crystal structure of the recombinant PLL·l-fucose complex confirmed that at least three sites were fucose-binding. Moreover, the crystal structures indicated that some of the other sites are masked either by the tetrameric nature of the lectin or by incorporation of the C terminus of the lectin into one of these sites. PLL exhibited an ability to bind to insect hemocytes and the cuticular surface of a nematode, H. bacteriophora.
Keywords: lektiny; krystalografie rentgenová; Protein Domains; bakteriální proteiny; Crystallography, X-Ray; Protein Structure, Quaternary; Bacterial Proteins; proteinové domény; fukosa; Fucose; Photorhabdus; Lectins; kvarterní struktura proteinů